Lictorella crassitheca Fraser 1941 - Calder, Dale R.; Choong, Henry H. C. (Zenodo, 2018)
Lictorella crassitheca Fraser, 1941b Lictorella crassitheca Fraser, 1941b: 85, pl. 18, figs. 12a, b. Zygophylax crassitheca .— Rees & Vervoort, 1987: 78. Holotype. USNM 43456: USA, Maine, 31 m, five fragments and some detached hydrothecae of a single colony, in fair condition, without gonophores, labelled “ type ”; ethanol. Type locality. USA: Gulf of Maine, 17 fm (31 m) (Fraser 1941b). Current status. Valid, as Zygophylax crassitheca (Fraser, 1941b). Remarks. Material designated by Fraser (1941b) as the “ type ” of Lictorella crassitheca at the NMNH (USNM 43456) presently comprises five fragments of what we regard as parts of a single colony. No indication of specimen number was provided in the original description. Rees & Vervoort (1987) referred to the collection as the “ type series,” but the specimen count in the online database of the NMNH is stated to be “1.” Recorded therein as a syntype, the specimen is taken here to be the holotype by monotypy (ICZN Art. 73.1.2). No other type material of the species is known to exist. Minimal collection data accompany the holotype. In addition to the record from the Gulf of Maine, Fraser (1941b) recorded this species from R/V Albatross Sta. 2430, 42°58’30”N, 50°50’W, SE of Sable Island (Nova Scotia, Canada), 179 fm (327 m), 23 June 1885. In being listed separately from the “ type ”, however, the material is not considered part of the type series (ICZN Art. 72.4.6). That collection, from the upper slope near the southern tip of the Grand Banks of Newfoundland, was not found in the current online database of the NMNH. In describing Lictorella crassitheca , no gonophores were observed by Fraser (1941b). Nematophores were said to be scarce and restricted to the polysiphonic hydrocaulus (Fraser 1941b, 1944a, b). Now assigned the binomen Zygophylax crassitheca , this species is currently recognized as valid (Rees & Vervoort 1987; Cairns et al . 2002; WoRMS). Published as part of Calder, Dale R. & Choong, Henry H. C., 2018, Names of hydroids (Cnidaria, ...